Os autores de mangá no Brasil: produção do aplicativo NanquimBR sob a lógica transmídia - Borges, Maria Tereza Batista (2017)
Mangas are one of the most important means of communication in Japan. Their history began in 1800 and, in the 20th century, they expanded throughout the world, leading the Japanese spirit and its strong cultural expression to various countries. That's how they came to Brazil and captured a legion of fans and artists who deciding to create their own mangas, based on the style of Japan, ally to their experiences. The proposal of the product of this work is to tell the story of these Brazilian authors of manga, through the realization of a transmedia production, whose main content is a geolocation app, the NanquimBR, based on augmented reality, to expand the user experience. For the construction of this project, we use the theoretical basis on transmedia, the history of the manga in the world and in Brazil, theories about culture of the convergence and paradigms, journalistic techniques, apps, geolocation and augmented reality. In addition, we talked to several manga authors through their first contact with Max Andrade, the author of Uberlândia, MG, who is writing manga since 2008 and has been win a Japanese art contest, the Silent Manga Audition. The idea of the transmedia app came in the second semester of the master's degree in Technology, Language and Society, and aims to create the means of dissemination and integration among Brazilian manga authors, since there is no space in the media for these productions, according to interviews and research performed. Thus, we intend to contribute to further research in the area and to the dissemination of works that are part of considered the ninth art worldwide.